PEMANFAATAN ULANG LIMBAH ORGANIK DARI SUBSTRAT TUBIFEX SP. DI ALAM UNTUK PERTUMBUHAN BOBOT TUBIFEX SP. - Sulistiyo, Andri; Widiastuti, Irawati Mei; Rizal, Ahmad (FAPETKAN UNTAD, 2012)
At this time the demand of Tubifex sp is be promoted. This is related to use of Tubifex sp. as fodder seeds that high nutritious. Utilization of organic waste from Tubifex sp. substrate in nature is one effort that can be done to get the maximum results in the business of cultivating Tubifex sp. This research aims to assess the influence of organic wastes of different weight to the absolute weight growth of Tubifex sp. and as information for people who want to cultivate Tubifex sp. These studies using Random Design Complete (RAL) with 4 treatments 5 times repetition, i.e. without the addition of organic wastes (A), the addition of organic wastes 750 g (B), the addition of organic wastes 1250 g (C) and the addition of organic wastes 1750 g (D). To know the influence of the treatment provided diversity analysis, used in the treatment of influential then continued with BNJ. Results of the study showed that the highest growth in absolute weights in treatment C (48,06 g) and the lowest at the treatment A (19.38 g). Further test results of BNJ indicates that treatments without the addition of organic wastes, the addition of organic wastes 750 g, the addition of organic wastes 1250 g and the addition of organic wastes 1750 g another is diferent very markedly. Key words : Growth, organic wastes, substrate, Tubifex sp.